2018
DOI: 10.1093/bioinformatics/bty357
|View full text |Cite|
|
Sign up to set email alerts
|

Distinguishing prognostic and predictive biomarkers: an information theoretic approach

Abstract: MotivationThe identification of biomarkers to support decision-making is central to personalized medicine, in both clinical and research scenarios. The challenge can be seen in two halves: identifying predictive markers, which guide the development/use of tailored therapies; and identifying prognostic markers, which guide other aspects of care and clinical trial planning, i.e. prognostic markers can be considered as covariates for stratification. Mistakenly assuming a biomarker to be predictive, when it is in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
62
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 64 publications
(63 citation statements)
references
References 25 publications
0
62
0
Order By: Relevance
“…Biomarkers that can predict responses to treatment would be valuable in supporting the paradigm shift towards personalized medicine [24][25][26]. In this study, univariate analysis identified several biomarkers that individually predicted responses to sarilumab treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Biomarkers that can predict responses to treatment would be valuable in supporting the paradigm shift towards personalized medicine [24][25][26]. In this study, univariate analysis identified several biomarkers that individually predicted responses to sarilumab treatment.…”
Section: Discussionmentioning
confidence: 99%
“…(1) we get the ML estimatorÎ ML (X ; Y ). It is well known that this estimator is biased (Steuer et al 2002), while there are many works that tried to derive expressions for correcting this bias. As Brillinger (2004) mentioned, the bias correction expressions are messy, and for that reason non-parametric procedures, such as jackknife (JK) or bootstrap, are preferable for estimating information theoretic terms.…”
Section: Frequentist Estimatorsmentioning
confidence: 99%
“…This can be done by performing sample size determination for observing given MI quantities with a particular statistical power [ 30 ]. Finally, by connecting the problem of multi-target FS with the problem of biomarker discovery in clinical trials with multiple endpoints, we can potentially use Group-JMI-Rand for deriving prognostic and predictive biomarkers in multiple endpoint trials [ 31 ].…”
Section: Discussionmentioning
confidence: 99%